Pemantauan Status Gizi Dan Edukasi Gizi pada Remaja Sebagai Upaya Pencegahan Stunting - Nia Budhi Asatuti; Ratih Nurani Sumardi; I Rai Ngardita; Sanya Anda Lusiana (ASMAT JURNAL PENGABMAS, 2021)
Abstract Stunting was one of the nutritional problems in many developing countries, including Indonesia. The long-term impact of stunting was the decreceof the quality of Human Resources (HR). There was many various of interventions, both sensitive intervension even specific intervension, have been carried out by the government to preventing stunting. Nutrition education, sexual education and reproductive health for adolescents was one of the planned special intervention activities. This community service aims to provide an overview of the problem of nutrition, education and stunting prevention in adolescents as one way to reduce stunting rates in the future. The location of this community service activity is at the SMP Baik Sentani, Jayapura Regency. The activities carried out were measuring nutritional status, anemia status and nutritional education related to stunting. After the activity there was an increase in students knowledge about stunting and anemia. Information about stunting and the role of adolescents in its prevention needs to be continued as a sensitive intervention effort to prevent stunting. Abstrak Stunting merupakan salah satu masalah gizi yang banyak dihadapi negara berkembang termasuk Indonesia. Dampak jangka panjang dari stunting adalah menurunnya kualitas Sumber DayaManusia (SDM).Berbagai intervensi baik sensitive maupun spesifik dilakukan pemerintah dalam pencegahan stunting. Pendidikan gizi masyarakat dan memberikan edukasi kesehatan seksual dan reproduksi serta gizi pada remaja merupakan salah satu kegiatan intervensi spesifik yang dicanangkan. Tujan pengabmas ini adalah memberikan gambaran masalah gizi, edukasi stunting dan pencegahannya pada remaja sebagai salah satu cara untuk menurunkan angka stunting di masa mendatang. Lokasi kegiatan pengabmas adalah SMP Baik Sentani Timur Kabupaten Jayapura. Kegiatan yang dilakukan adalah pengukuran status gizi, status anemia dan edukasi gizi terkait stunting. Setelah kegiatan terjadi peningkatan pengetahuan siswa mengenai stunting dan anemia. Informas itentang stunting dan peran remaja dalam pencegahannya perlu terus dilakukan sebagai upaya intervensi sensitive pencegahan stunting.